Multiple Site-Specific One-Pot Synthesis of Two Proteins by the Bio-Orthogonal Flexizyme System - Xiao, Qiuyun; Liu, Zihan; Zhao, Xuan; Xiong, Hai (Frontiers in Bioengineering and Biotechnology, 2020)
Acetylation of lysine is a reversible post-translational modifications (PTMs), which plays a key role in regulating gene expression and dynamic transitions in chromatin remodeling. Here, we have developed the first one-pot bio-orthogonal Flexizyme systems: the acetyl-lysine (AcK) and non-hydrolyzable thioacetyl-lysine (ThioAcK) were site-specifically incorporated into human histone H3 and H4 at different lysine positions in vitro, either individually or in pairs. In this study, we demonstrated its high efficiency and accuracy toward one-pot synthesis of two desired histone variants.